An enigmatic kilometer-scale concentration of small mytilids (Late Miocene, Guadalquivir Basin, S Spain) - Aguirre, Julio
UpperMiocene heterozoan carbonates crop out extensively in a NE–SW-trending belt (42 km long and 1.5–8 km wide) along the so-called El Alcor topographic high, fromCarmona to Dos Hermanas (Seville, S Spain). These carbonates formed at the southern active margin of the Guadalquivir Basin, the foreland basin of the Betic Cordillera. They change to marls basinward (NE) and to sands landward (SE and SW). Therefore, carbonate production was constrained to a limited area in an otherwise siliciclastic shelf. The carbonates (up to 40 m thick) overlie a gradually coarsening-upward succession of marls followed by silts and sandstones. The carbonate sequence can be divided into three subunits corresponding, frombottom to top, to lowstand, transgressive, and highstand system tract deposits. The lower subunit, exhibiting extensive trough cross-bedding, is interpreted as a shallow-water bar deposit. The intermediate subunit onlaps underlying sediments and was deposited in deeper, lowturbulence conditions. The upper subunit deposits accumulated in a well-oxygenated outer platform based on benthic foraminiferal assemblages. The presence of hummocky and swaley cross-stratification in these latter deposits suggests that theywere affected by storms. Pervasive fluid-escape structures are also observed throughout the carbonates. The three subunits consist of bioclastic packstones to rudstonesmade up of abundant fragments of smallmytilids. Isotopic data from serpulid polychaete Ditrupa tubes show 13C-depleted values (up to −16.1‰), whereas δ18O yields normal marine values. Additional isotopic data on shells of scallops, oysters, and small mussels, as well as bulk sediment, show diagenetic alterations. Based on actualistic examples of massive concentrations of mussels, the nearly monospecific composition of the El Alcor deposits, together with negative δ13C values of Ditrupa tubes, indicates that cold seeps presumably promoted carbonate formation. However, the absence of typical features of cold-seep deposits, such as authigenic carbonatesmediated by anaerobic bacterial activity and the typical chemosynthetic shelly organisms, makes the large carbonate body of El Alcor an unusual cold-seep deposit.